Peran pendidikan pancasila dalam memperkuat identitas nasional studi literatur - Abdillah, ’Ibrah Rahman (Maliki Interdisciplinary Journal, 2026)
This study aims to analyse the role of Pancasila education in strengthening national identity through literary analysis. The study employs a qualitative approach by gathering data from journals, articles, and various relevant references about Pancasila education and national identity. The study’s findings indicate that Pancasila education has a crucial role in fostering a sense of nationalism, tolerance, and air quality in younger generations. In the age of globalisation, Pancasila education has become a strategic tool for addressing the impact of local culture that might undermine national identity. The use of Pancasila principles in education has the potential to enhance the persatuan and kebangsaan of Indonesian society. Because of this, Pancasila education must continue to be innovative in order to be relevant with the changing times and the needs of future generations.